Engineering maintenance a modern approach - Dhillion, B. S. (Balbir S.), 1947- (CRC Press, 2002)
A text for upper-level undergraduates and graduate students in mechanical and industrial engineering, maintenance and operations, and equipment design. Dhillon (U. of Ottawa) discusses an overarching strategy to preserve equipment function, avoid the consequences of equipment failure, and ensure productive capacity. The text covers topics including quality and safety, human error, software maintenance considerations, cost, reliability, and maintainability.